FRI0389 Effects of Chronic Treatment with Subcutaneous Blisibimod on Renal and Inflammation Biomarkers in Subjects with Systemic Lupus Erythematosus in Phase 2 PEARL-SC and Open-Label Extension Studies. (10th June 2014) - Richard, F.A.; Scheinberg, M.A.; Thomas, M.; Chu, A.D.; Hislop, C.; Martin, R.S.; Petri, M.
Abstract : Background: Blisibimod is a peptibody that inhibits B-cell activating factor (BAFF). Significant improvements in secondary evaluations of SLE disease activity including proteinuria were reported previously[1] from the Phase 2 randomized, double-blind, placebo-controlled trial with subcutaneous blisibimod in patients with SLE, PEARL-SC (Phase 2b, NCT01162681 ). Objectives: To evaluate whether the effects on renal biomarkers, observed in patients who received blisibimod in the PEARL-SC study were durable through continued dosing in the open-label extension trial (OLE, NCT01305746 ). Methods: 547 subjects with serologically-active SLE and SELENA SLEDAI ≥6 were randomized to self-administer blisibimod (200 mg monthly SC, 100 mg weekly SC, 200 mg weekly SC) or regimen-matched placebo in the PEARL-SC study. The subjects received drugs for up to 52 weeks (median 37 weeks). At baseline 76 subjects had renal involvement using SELENA-SLEDAI definitions. A total of 382 subjects enrolled in the OLE study and received blisibimod. Here we report the effects of blisibimod on inflammation biomarkers in the PEARL-SC study and in those subjects in the OLE study who had initiated blisibimod therapy in the PEARL study (N=277) and continued through the interim analysis of the OLE study in March 2013. In addition, we report treatment effects on renal biomarkers in 2 renal subgroups defined as (i) baseline proteinuria ≥0.5 g (determined from random urines, N=41), or (ii) baseline proteinuria ≥1g (N=25). Results: Significant reductions in proteinuria reported in the PEARL-SC study reductions in proteinuria were observed with blisibimod, compared to baseline, from Week 12 through Week 52 in the subgroup of subjects with baseline protein/creatinine ratio (Pr/Cr) ≥1 (Figure 1 A) and through Week 44 in those with baseline Pr/Cr ≥0.5. These effects were durable through 52 weeks of open label treatment. When compared with response in the patients randomized to placebo in PEARL-SC, there was a tendency toward increases in mean GFR in the patients receiving blisibimod at Week 24 in both renal subgroups with mean ΔGFR =1.4 and -3.0 mL/min [N=36, 37], for blisibimod and placebo respectively, in the subgroup with baseline Pr/Cr ≥0.5. Reductions in titers of anti-double-stranded DNA (dsDNA) antibodies and increases in complement C3 and C4 compared with baseline were observed through 52 weeks of blisibimod therapy (Figure 1 B, C and D). Blisibimod was safe and well-tolerated at all dose levels with no meaningful imbalances in serious adverse events or infections between blisibimod and placebo in the PEARL-SC study, and continued to be well-tolerated through the OLE study. Conclusions: These data demonstrate that blisibimod induces durable effects on proteinuria and renal biomarkers. Clinical studies are ongoing to evaluate the effects of blisibimod in patients with SLE (including renal manifestations) and IgA nephropathy. References: Furie RA, Scheinberg MA, Leon G, et al. Arthritis Rheum. 2012;64(12):4169. Disclosure of Interest: F. Richard Consultant for: Anthera Pharmaceuticals, M. Scheinberg: None declared, M. Thomas: None declared, A. Chu: None declared, C. Hislop Employee of: Anthera Pharmaceuticals, R. Martin: None declared, M. Petri Consultant for: Anthera Pharmaceuticals DOI: 10.1136/annrheumdis-2014-eular.5593